How to make music in an epidemic : popular music making during the AIDS crisis, 1981-1996 - Jones, Matthew J. (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This volume examines responses to the epidemic of HIV/AIDS in Anglophone popular musicians and music video during the AIDS crisis (1981-1996). Through close reading of song lyrics, musical texts, and music videos, this book demonstrates how music played an integral part in the artistic-activist response to the AIDS epidemic, demonstrating music as a way to raise money for HIV/AIDS services, to articulate affective responses to the epidemic, to disseminate public health messages, to talk back to power, and to bear witness to the losses of AIDS"--
Introduction -- Palimpsests -- Intertexts -- Pedagogies -- Conspiracies -- Testimonials -- Epilogue.
Keywords: AIDS (Disease) -- Songs and music -- History and criticism; Popular music -- 1981-1990 -- History and criticism; Popular music -- 1991-2000 -- History and criticism; AIDS (Disease) -- Social aspects; MUSIC / Genres & Styles / Pop Vocal